SR/RS Motifs as Critical Determinants of Coronavirus Life Cycle - Nikolakaki, Eleni; Giannakouros, Thomas (Frontiers in Molecular Biosciences, 2020)
SR/RS domains are found in almost all eukaryotic genomes from C. elegans to human. These domains are thought to mediate interactions between proteins but also between proteins and RNA in complex networks associated with mRNA splicing, chromatin structure, transcription, cell cycle and cell structure. A precise and tight regulation of their function is achieved through phosphorylation of a number of serine residues within the SR/RS motifs by the Serine-arginine protein kinases (SRPKs) that lead to delicate structural alterations. Given that coronavirus N proteins also contain SR/RS domains, we formulate the hypothesis that the viruses exploit the properties of these motifs to promote unpacking of viral RNA and virion assembly.